Sickle cell considerations in athletes - Eichner, E. R. (Clinics in Sports Medicine, 2011)
This article highlights the exertional-sickling collapse syndrome in athletes with sickle cell trait (SCT). It covers all aspects of this syndrome, including pathophysiology, new research on microcirculatory changes, clinical features, differential diagnosis, prevention, and treatment. Also covered in this article are other clinical concerns for athletes with SCT, including lumbar myonecrosis, splenic infarction, hematuria, hyposthenuria, and venous thromboembolism. The final section offers practical points on athletes with sickling hemoglobinopathies more serious than SCT.